Israeli survey of anesthesia practice related to placenta previa and accreta. Issue 4 (24th November 2015) - Ioscovich, A.; Shatalin, D.; Butwick, A. J.; Ginosar, Y.; Orbach‐Zinger, S.; Weiniger, C. F.
Abstract : Background: Anesthesia practices for placenta previa (PP) and accreta (PA) impact hemorrhage management and other supportive strategies. We conducted a survey to assess reported management of PP and PA in all Israeli labor and delivery units. Methods: After Institutional Review Board waiver, we surveyed all 26 Israeli hospitals with a labor and delivery unit by directly contacting the representatives of obstetric anesthesiology services in every department (unit director or department chair). Each director surveyed provided information about the anesthetic and transfusion management in their labor and delivery units for three types of abnormal placentation based on antenatal placental imaging: PP, low suspicion for PA, and high suspicion for PA. The primary outcome was use of neuraxial or general anesthesia for PP and PA Cesarean delivery. Univariate statistics were used for survey responses using counts and percentages. Results: The response rate was 100%. Spinal anesthesia is the preferred anesthetic mode for PP cases, used in 17/26 (65.4%) of labor and delivery units. By comparison, most representatives reported that they perform general anesthesia for patients with PA: 18/26 (69.2%) for all low suspicion cases of PA and 25/26 (96.2%) for all high suspicion cases of PA. Although a massive transfusion protocol was available in the majority of hospitals (84.6%), the availability of thromboelastography and cell salvage was much lower (53.8% and 19.2% hospitals respectively). Conclusions: In our survey, representatives of anesthesia labor and delivery services in Israel are almost exclusively using general anesthesia for women with high suspicion for PA; however, almost two‐thirds use spinal anesthesia for PP without suspicion of PA. Among representatives, we found wide variations in anesthesia practice patterns with regard to anesthesia mode, multidisciplinary management, and hemorrhage anticipation strategies.